Evidence for infectious merozoites of Plasmodium falciparum from natural isolates of cultured hepatoma cells infected with sporozoites - Olumide Adeyemi; Akinniyi Osuntoki; Olubunmi Magbagbeola; Muzamil Mahdi Abdel Hamid; Arwa Elaagip; Ann-Kristin Mueller; Muntaser Ibrahim (PLoS ONE, 2025)
Previous cell culture systems using various human hepatoma cell lines established that the intra-hepatic stages of Plasmodium falciparum could be studied ex vivo. However, only one of these culture systems yielded infective merozoites that subsequently completed the parasite’s life cycle outside a human host. We hypothesized that a major limitation is the use of laboratory-adapted P. falciparum blood stages for sporozoites generation. Plasmodium falciparum sporozoites were generated by membrane-feeding of gametocyte-infected blood samples from hospital patients to Anopheles arabiensis. Subsequently, cultured HepG2 cells were infected with the sporozoites. From 6 days post-sporozoite inoculation, liver merozoites could be harvested from the cell supernatants. When co-cultured with O + erythrocytes, these merozoites established a blood infection and yielded erythrocytic stage parasites that re-infected erythrocytes. To confirm that the erythrocytic parasites generated were P. falciparum, RNA expressed by the erythrocytic parasites was isolated and used as control in microarray analysis against RNA expressed by irradiated erythrocytic parasites; subsequently, P. falciparum genes were identified. The cultured HepG2 cells permitted the full intra-hepatic maturation of P. falciparum parasites from natural isolates. Infective merozoites were yielded which gave rise to the erythrocytic stage P. falciparum post-infection into O + erythrocytes. The full intra-hepatic maturation of the naturally isolated P. falciparum parasites in a HepG2 cell culture system is possible. This finding has important implications for malaria research and vaccine development.